FM-DBEM Simulation of 3D Microvoid and Microcrack Graphite Models - Houdi Lu; Hongtao Wang; Haitao Wang; Lie Jin; Xinxin Wu; Yu Zhou (Science and Technology of Nuclear Installations)
The graphite is porous medium, and the geometry and size distribution of its structural deficiencies such as microcracks and microvoids at different oxidation degrees have a great influence on the overall performance. In this paper, we adopt the FM-DBEM to study 3D models which contain spheroidal microvoids and circular microcracks. The accuracy of this method is tested by a comparison to the theoretical solution to the problem of 2D microcrack and microvoid interaction problem. Two simulations are conducted: the simulation of graphite model containing a large number of randomly distributed microcracks and microvoids and the simulation of graphite model containing microcracks and growing microvoids. The simulations investigate the effective moduli versus the two microstructures’ density and the effect of microvoid’s growth on the SIF of microcrack.